2021
DOI: 10.1177/0361198121995827
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Regression Model Structure for the HCM-6 Equal-Capacity Passenger Car Equivalency Methodology

Abstract: In the current version of the Highway Capacity Manual (HCM-6), equal-capacity passenger car equivalencies (EC-PCEs) are used to account for the effect of trucks for capacity analyses. The EC-PCEs for freeway segments were estimated using a microsimulation-based methodology where the capacities of the mixed-traffic and car-only flow scenarios were modeled. A nonlinear regression (NLR) model was used to develop capacity adjustment factor (CAF) models using the microsimulation data as input. The NLR model has a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The desired speed distributions are obtained from the field data when the traffic is under free-flow conditions. It should be noted that the speed distributions are disaggregated by vehicle type (e.g., cars and trucks) because it has been shown that in the western U.S. free-flow speeds can vary greatly according to vehicle type ( 19, 20 ). In addition, the desired speed distributions are disaggregated by locations (i.e., PDMS1 versus PDMS2) and by displayed messages (i.e., SLOW versus STOP).…”
Section: Microscopic Traffic Simulation Modelmentioning
confidence: 99%
“…The desired speed distributions are obtained from the field data when the traffic is under free-flow conditions. It should be noted that the speed distributions are disaggregated by vehicle type (e.g., cars and trucks) because it has been shown that in the western U.S. free-flow speeds can vary greatly according to vehicle type ( 19, 20 ). In addition, the desired speed distributions are disaggregated by locations (i.e., PDMS1 versus PDMS2) and by displayed messages (i.e., SLOW versus STOP).…”
Section: Microscopic Traffic Simulation Modelmentioning
confidence: 99%